Pipelines to Pathways: Medical School Commitment to Producing a Rural Workforce. Issue 4 (26th November 2020) - Longenecker, Randall L.; Andrilla, C. Holly A.; Jopson, Andrew D.; Evans, David V.; Schmitz, David; Larson, Eric H.; Patterson, Davis G.
Abstract: Purpose: Despite the efforts of numerous medical schools to produce rural physicians, many rural communities in the United States still experience physician shortages. This study describes the current landscape of rural efforts in US undergraduate medical education and catalogs medical school characteristics and activities that evidence has suggested, and that many experts in rural medical education believe, may result in more graduates choosing rural practice. Methods: This is a descriptive study of publicly available and rurally relevant characteristics of all 182 allopathic and osteopathic medical schools operating in the 50 states and the District of Columbia in 2016, with rural program information for these schools updated in 2019. The authors constructed a "rural program" definition in order to systematically catalog coordinated and strategic medical school efforts to produce a rural physician workforce. Findings: Few (8.2%) medical schools expressed an explicit commitment to producing rural physicians in public mission statements. However, most (64.8%) provided rural clinical experiences and many demonstrated their commitment in other ways. Only 39 (21.4%) did so through a formal rural program. Conclusions: In establishing an explicit rural program definition and documenting other markers of rural commitment, this paper provides a baseline for future studies of rural workforce production and medical school investment in these programs, activities, and personnel. Demonstrating the effectiveness of schools' rural physician education efforts will require collaboration across institutions and more intensive evaluations of programs involving students who, though relatively few in number, have great potential for contributing to the health of rural communities across the nation.